Spatiotemporal variation of the bacterioplankton community in the German Bight: from estuarine to offshore regions. Issue 1 (December 2016) - Lucas, Judith; Wichels, Antje; Gerdts, Gunnar
Abstract Marine microbial biogeography has been studied intensively; however few studies address community variation across temporal and spatial scales simultaneously so far. Here we present a yearlong study investigating the dynamics of the free-living and particle-attached bacterioplankton community across a 100 km transect in the German Bight reaching from the Elbe estuary towards the open North Sea. Community composition was assessed using automated ribosomal intergenic spacer analysis and linked to environmental parameters applying multivariate statistical techniques. Results suggest that the spatial variation of the bacterioplankton community is defined by hydrographic current conditions, which separate the inner German Bight from the open North Sea and lead to pronounced differences in the coastal and offshore bacterioplankton community. However this spatial variation is overwhelmed by a strong temporal variation which is triggered by temperature as the main driving force throughout the whole transect. Variation in the free-living community was predominantly driven by temperature, whereas the particle-attached community exhibited stronger spatial variation patterns.